Earliest evidence of sedentism in the Antilles: Multiple isotope data from Canímar Abajo, Cuba - Yadira Chinique de Armas; Silvia Teresita Hernández Godoy; Luis M. Viera Sanfiel; William M. Buhay; Jason E. Laffoon (Proceedings of the National Academy of Sciences, 2025)
The early populations that inhabited the Antilles were traditionally understood as highly mobile groups of hunters/fishers and gatherers. Although more recent data have demonstrated that some populations engaged in the production of domestic plants and cultivars, questions remain about other aspects of their lifeways, including whether the adoption of domesticates was accompanied by a decrease in residential mobility. The level of sedentism in a population is an instrumental variable to understand community social relations and complexity, adaptations, and lifeways. Here, we combined enamel strontium ( 87 Sr/ 86 Sr), oxygen (δ 18 O en ), and carbon (δ 13 C en ) isotopes of 44 human teeth from the site of Canímar Abajo—where the oldest human remains from the insular Caribbean have been reported—to examine the mobility patterns of early Antillean groups. In contrast with traditional narratives, the homogeneous strontium isotope values observed in most individuals from the older funerary area of the site (cal. BC 2237–790) were consistent with the pattern expected for a sedentary population subsisting primarily on local resources obtained close to the coast. The isotopic evidence reveals that between cal. AD 403–1282, the mound was reused for funerary practices by both local communities and nonlocal individuals. The evidence suggests that this period saw higher population mobility, with influxes of individuals from more distant locations and diverse dietary and burial traditions. The isotope results from Canímar Abajo provide the earliest isotopic evidence of populations with low-level residential mobility in the Antilles.